ESTIMASI RELATIVE SURVIVAL DENGAN LIFE TABLE DAN METODE HAKULINEN-TENKANEN - , WIDYA PRATESA ARYAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Relative survival methods are used to compare the survival experience with the one expected of population mortality rates. These methods are useful when the cause-specific death information is not accurate or not available. Relative survival is the ratio of the observed survival proportion to the expected survival proportion. The aim of this paper is to estimated the relative survival rates with life table Ederer II and to modeled the relative survival rates with Hakulinen-Tenkanen approach